Representações de brinquedos, relevos e descrição oral por crianças com deficiência visual - Ferroni, Giovana Mendes (2016)
The research objective was to analyze the repertory of representations of means of transportation also called “vehicles” (Aircraft, bicycle, car, sail boat, train and helicopter) expressed in modeling clay, drawing and oral description of children with visual deficiency with the use of models like toys, or reliefs or the reading of the description of a mean of transportation made by the child itself. Participating in the study were two boys with congenital blindness (A and N) and two girls with low vision (G and K) with visual deficiency without any other deficiency associated, with ages between six and nine years old. The research was developed in two institutions frequented by the participants. One of them non-governmental and the other municipal, both specialized in the caring of people with visual deficiency, and localized in two midsize cities in the intern of São Paulo State, where the participants were receiving caring. A period of familiarization between researcher and participant preceded the data collect. The procedure of data collect was made in the following sequence of steps: Repertoire Survey, Intervention, Replication of the repertoire survey and creation of a mean of transportation. The Intervention consisted in presenting the participants the models: toy, relief and orally reading the oral description made by the child itself. In front of each model the children were requested to say the name of the object presented, play the model on a sequence of activities in which they used the modeling clay, pencil and paper to do a drawing and the oral production of the model which was worked on both previous conditions (modeling and drawing). During the confection of the representations the children answered questions about the characteristics and functions of the object presented. The data analysis guided itself by: 1- The component elements featured by the children and the characteristics attributed by them to the mean of transportation in the representations by modeling, drawing and oral description; 2- the type of model used during the intervention: toy, relief and reading of the oral description; 3- the creation of a vehicle using modeling clay, drawing and description. The results showed that, in the absence of models, in dealing with the component elements, the participants with low vision highlighted the external in their productions, for example, wheel, door, while the blind highlighted the internal, like, seat, steering wheel. However, when toys or reliefs were presented, the blind participants also highlighted in their productions the external elements. In the oral description, it was noted that all the children described above all the component elements and the aspects of the function played by them or the vehicles. However, in the oral descriptions of toy models or relief, they referred proportionally more times to the component elements. In reference to the used models in the intervention, the results indicated modifications in the drawing representations, modeling and oral description of the participants, if compared to the productions in the absence of the models. When there was the presentation of the toys to the blind participant, his productions in modeling clay were made on the same representation pattern of the toy, while that the drawing was made in a superior point of view, that is an object seen from the top. When there was the presentation of a relief model, the productions in drawing and modeling clay of the blind participant followed the flat point of view of the relief representation. When the reading of the oral description happened, the representations of the blind participant didn’t change. As to participant K, with low vision, the representations remained adopting the flat point of view for the three types of model. About the vehicle creation step, highlight itself that participant K, with low vision, created a new mean of transportation. The other participants (A, N and G) made means of transportation that had been worked during the intervention. The results empirically proved that the productions of the children with visual deficiency are different from the ones produced by children that can see, seen that they organize the world the notice by other sensorial channels other than the vision. This results were deep-set with the findings about the differences of production between children with visual deficiency. The representations of the blind children and of the ones with low vision considered different points of view; this results contribute to the discussion about the comparing between psychic children, children with visual deficiency/blindness and children with visual deficiency/low vision. It is believed that the results obtained in this work contribute to the discussions, even sparse, about the representations of children with visual deficiency.